2019
DOI: 10.3847/1538-4365/ab3415
|View full text |Cite
|
Sign up to set email alerts
|

The Gas Kinematics, Excitation, and Chemistry, in Connection with Star Formation, in Lenticular Galaxies

Abstract: We present results of long-slit and panoramic spectroscopy of extended gaseous disks in 18 nearby S0 galaxies, mostly in groups. The gas in our S0s is found to be often accreted from outside that is implied by its decoupled kinematics: at least 5 galaxies demonstrate strongly inclined large-scale ionized-gas disks smoothly coupled with their outer HI disks, 7 galaxies reveal circumnuclear polar ionized-gas disks, and in NGC 2551 the ionized gas though confined to the main galactic plane however counterrotates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 108 publications
(148 reference statements)
7
35
0
Order By: Relevance
“…In principle, it can be accretion of primeval gas from a cosmological filament because the current ratio of stellar-to-gas mass in the ring, which is approximately 8:1, places the chemical evolution of the ring of NGC 4513 in the "gas-depleted" stage (Zahid et al 2014;Ascasibar et al 2015), meaning that the current metallicity of the ionised gas must correspond to the saturation level, which is close to the solar value (Zahid et al 2014;Ascasibar et al 2015), independently of the initial gas metallicity. This may explain the proximity of the gas oxygen abundance in the ring of NGC 4513 to the common value found by us for a number of other outer rings in S0 galaxies (Sil'chenko et al 2019).…”
Section: Star Formation In the Outer Ring Of Ngc 4513supporting
confidence: 82%
See 2 more Smart Citations
“…In principle, it can be accretion of primeval gas from a cosmological filament because the current ratio of stellar-to-gas mass in the ring, which is approximately 8:1, places the chemical evolution of the ring of NGC 4513 in the "gas-depleted" stage (Zahid et al 2014;Ascasibar et al 2015), meaning that the current metallicity of the ionised gas must correspond to the saturation level, which is close to the solar value (Zahid et al 2014;Ascasibar et al 2015), independently of the initial gas metallicity. This may explain the proximity of the gas oxygen abundance in the ring of NGC 4513 to the common value found by us for a number of other outer rings in S0 galaxies (Sil'chenko et al 2019).…”
Section: Star Formation In the Outer Ring Of Ngc 4513supporting
confidence: 82%
“…5. Comparison of the gas oxygen abundance in NGC 4513 to that of other outer rings of S0s (Proshina et al 2019;Sil'chenko et al 2019) reveals exactly the same metallicity: for a sample of a dozen gaseous outer rings in S0s, mostly with corotating kinematics (though in NGC 2551 the gas counter-rotates), we find [O/H] = −0.15 dex (Sil'chenko et al 2019).…”
Section: Gas-phase Metallicitysupporting
confidence: 56%
See 1 more Smart Citation
“…Molaeinezhad et al 2019). In Katkov et al (2014Katkov et al ( , 2015, Proshina et al (2019), andSil'chenko et al (2019), the authors discuss the origin of this counter-rotating gas and argue that S0s might accrete gas probably from filaments or from minor mergers. In parallel, numerous works have shown that S0s can be produced by galaxy mergers including major mergers (Bekki 1998;Querejeta et al 2015;Tapia et al 2017;Eliche-Moral et al 2018) as well as minor mergers (Bournaud et al 2005;Bekki & Couch 2011).…”
Section: Star-forming S0smentioning
confidence: 99%
“…Due to the dynamical configuration observed, with the gas significantly misaligned and in a polar configuration with respect to the major axis of the galaxy, the origin of the gas can be clearly identified as external, as also seen for several other galaxies in similar configurations (e.g. Sil'chenko et al 2019, Gnilka et al 2020, as secular processes are not able to explain large quantities of misaligned gas (Caldwell et al 1986, Kannappan & Fabricant 2001. The properties of NGC 5077 match rather well the predictions from numerical simulations by van de Voort et al (2015), where an early type galaxy can show a misaligned gas distribution caused by late-time gas accretion after a gas-rich major merger.…”
Section: Origin Of the Gasmentioning
confidence: 52%